Evaluation of Preliminary Phytochemical Constituents and Antibacterial Activity of Edible Plants against Urinary Tract Infection Causing Bacteria in Children - Arun Thangavel; Omprakash Sahu; Saravanan Ponnappan; Abenezer Tadele; Gezahegn Abawa; Karthikeyan M (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
The present study is aimed to determine the preliminary phytochemical screening and antibacterial activity of acetone extract of the edible plants, Solanum nigrum (L.), Murraya koenigii (L.), Sesbania  grandiflora (L.) against urinary tract infection causing bacteria in children. These edible plant extracts were checked for their antibacterial activity by the agar disc diffusion method. The preliminary phytochemical screening of this extract revealed the presence of alkaloids, proteins, amino acids, anthraquinone glycosides, flavonoids, tannins, phenolic compounds, carbohydrates, saponins and steroids. In the Kirby-Bauer disc diffusion method, Ciprofl oxacin showed the high zone formation against all the isolated bacterial strains. Among all the extracts, Murraya koenigii (L.) from winter season showed maximum inhibitory activity for all the isolated bacterial strains. The minimal inhibitory concentration values of the acetone extract of these three edible plants from two different seasons against the isolated bacterial strains were observed. The acetone extracts of these edible plants have a broad spectrum of antibacterial activity and support the traditional use of these plants as medicines.